Analisis Kaidah Fiqhiyyah al-'Adatu muhakkamah Terhadap Metode Istinbath Hukum Kajian Hukum Keluarga Islam - Antoni Yoseph; Hendri Sayuti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the application of the fiqhiyyah al-'Adatu Muhakkamah principle (customary law can be established as law) in the istinbath (inference) method of Islamic family law. The main focus of this study is to explore the extent to which community traditions or customs can be used as a basis for formal legality in domestic matters such as dowry, alimony, and the division of joint property. This research is a qualitative study using a library research approach, employing descriptive-analytical methods to analyze usul fiqh books and family law regulations in Indonesia (Compilation of Islamic Law). The results of the study show that the principle of al-'Adatu Muhakkamah plays a crucial role as an instrument of flexibility in Islamic law, whereby the law can change according to changes in time and place as long as it does not contradict explicit textual evidence (sharih). In the context of family law, this rule is implemented in determining the standard of alimony (ma'ruf) and recognition of joint property (gono-gini), which is a crystallization of the customs of the Indonesian people. In conclusion, the integration of customs through this rule provides space for Islamic family law to remain relevant, fair, and applicable in responding to the socio-cultural dynamics of contemporary society.